A fragment of the translation of Prosper Mérimée’s book Histoire de Don Pèdre, roi de Castille, and the translator’s commentary - O. V. Smolitskaya (Шаги, 2022)
The book by the famous 19th century French writer Prosper Mérimée is devoted to Spain of the 14th century. The book focuses on the life of King Pedro I of Castile named the Cruel and his struggle for the throne against his half-brother Don Enrique, illegitimate son of his father. The author describes in detail the domestic and foreign policy of Don Pedro, shows how his severity, initially aimed at centralization of the state and curbing the will-fulness of the “seigneurs”, turns into unjustified cruelty, suspicion and vindictiveness. This pushes internal and external supporters away from of the king and inevitably leads to his death. The book is based on medieval chronicles, while at the same time the writer reflects on History itself, on the role of a particular person in historical events, and on the possibility of moral choice in a time of troubles. The book is translated into Russian for the first time. The translator faced the problems of transferring the stylistic diversity of the book, where the impassive narrative of Mérimée-the-historian alternates with the emotionally tense language of Mérimée-the-artist, as well as the problem of conveying in Russian the realities of medieval Spain.